Simulation and experimental study of biogas explosion - Nurul Syazwana, Noor Azmi (2021)
Biogas is an attractive substitute to conventional petroleum fuels because they have the advantages of being very cheap and are renewable in nature, and thereby not contributing to the net atmospheric concentration of the greenhouse gas, carbon dioxide. Several techniques have been developed to prevent the destructive damage to biogas plants in industries. Studies on vented gas and dust explosions have shown the evolution of venting area with pressure depending on the nature and state of the explosive mixture (composition, initial pressure and temperature, pre-ignition turbulence) and on the vessel characteristics (dimension, shape, presence of obstacles and others). An understanding of the mechanisms by which pressure is generated in vented explosions is important in the design of explosion reliefs and to the investigation of incidents. Another approach using venting system also included venting with a presence of venting duct. While venting devices are common solutions for the mitigation of accidental explosions in industrial equipment, study about duct venting are still very small. Researches on biogas explosion in cylindrical vessel are also very limited. In this study, the investigation of explosion characteristics of the premixed biogas-air and methane-air were analysed through the explosion maximum overpressure and flame speed. The factors that contributed to the premixed fuels-air explosions characteristics was evaluated which are the venting duct length and diameter, the mixture concentration as well as the presence of carbon dioxide by comparing biogas-air and methane-air explosions. Moreover, the flame propagation of fuels-air in duct vented and simply vented explosion were investigated by using numerical simulation. The numerical results were compared with the observation from experimental works. From the observation of 2D pressure contours for both duct vented and simply vented explosion obtained from Fluent, for duct vented explosion, the pressure readings were at maximum at two areas of the pipe. The presence of the duct affected the flame area and consecutively the overpressure recorded while for the simply vented (ductless) explosion, the contour gave observations of a simpler reaction and flame propagation. From the evaluation, the effect of different duct length proved that the highest maximum overpressure recorded for both gases were at duct length of 0.50 m. The overpressure recorded were 4.66 bar and 5.99 bar as well as 146.22 m/s and 149.65 m/s of flame speed for biogas-air mixture and methane-air mixture respectively. Apart from that, for factor of different duct diameters, the highest maximum overpressure and flame speed recorded for both mixtures are at 0.05 m (4.66 bar and 146.22 m/s for biogas-air while 5.99 bar and 149.65 m/s for methane-air mixtures). In the meantime, the investigation on effect of mixture concentration on maximum overpressure and flame speed shows the highest values for these two explosion characteristics were recorded at ER=1 which is stoichiometric condition. All the experimental works validate the simulation works by carrying the experiment along the pipe for different ER. Apart from that, based on the recorded maximum overpressure in experimental works of biogas-air and methane-air mixtures explosions, it can be elucidated that methane produced higher explosion severity than biogas. This was due to the dilution effect of CO2, which has a higher heat capacity than methane. Lastly, both graphs of maximum overpressure versus time from numerical and experimental works were presented and studied. Besides several differences mentioned previously, the graphs were in agreement with each other. The differences might be due to the assumption made in ANSYS Fluent and only a simple chemical reaction equation was considered in the model.